Understanding science and technology in the development of a chemical industry - UMP, PNC
Universiti Malaysia Pahang (UMP) recently organised a public lecture that highlighted lessons learned from issues rose from the rare earth refinery plant operated at Lynas Advanced Material Plant (LAMP) in Gebeng, Kuantan.